Extended applications of the advanced data validation and reconciliation method in studies of energy conversion processes. (15th October 2018) - Szega, Marcin
Abstract: Achievement of satisfactory results of measurements data reconciliation in energy conversion processes is possible only in the case of application of the so-called generalized advanced method of data validation and reconciliation. An application of this method made it possible to complete the validation model of the process (conditional equations of optimization task) including substance and energy conservation principles with additional equations describing energy conversion processes. The criterion of selection of the form of additional equations in the validation model in reconciliation calculation has been formulated based on the derived characteristic property of variables uncertainty after data reconciliation. The developed methodology has been used for example calculations of data reconciliation in the selected steam power unit. At the design stage of energy conversion systems, the problem of the number of redundant measurements, as well as their location, appears. Example calculations for the redundant measurement systems of selected energy conversion processes have been carried out. As objective functions of the combinatorial optimization tasks, the relative uncertainty of the selected energy effectiveness indicators was assumed. The results of calculations confirm the influence of the number of redundant measurements and their location in the measurement systems on the accepted criteria of optimization. An idea to apply in the data reconciliation method the measurements uncertainties expressed by fuzzy numbers has been presented. As a criterion for comparison of the results of calculations for both types of uncertainties, the relative entropy of information as well as the complex standard uncertainties of main assessment indicators of analysed combined heat-and-power unit operation supervision has been chosen. The advanced data validation and reconciliation method was introduced and developed in Poland to the thermodynamic analyses of energy conversion processes by professor Jan Szargut. The above issues constitute further researches on the development and application of this method in thermodynamics analyses performed by the author of this paper. Highlights: Derivation of criteria of generalized (unified) advanced data validation task enlargement. Application of the generalized data validation and reconciliation in thermal technology. Optimization of a location of redundant measurements in energy conversion processes. Data validation and reconciliation task using fuzzy measurements uncertainties. Application of the information entropy in the assessment of the measurement systems.